Lasers for Flow Cytometry: Current and Future Trends. Issue 1 (18th January 2018) - Shapiro, Howard M.; Telford, William G.
Abstract: Lasers are the principal light sources for flow cytometers. Virtually all cytometers are equipped with at least one (and often many more) lasers. This unit covers the various types of lasers available and the qualities that make them suitable or unsuitable for use in flow cytometers. Also included is a discussion of future directions, particularly in the area of tunable laser development. Practical tips are provided for building multilaser cytometer systems. © 2018 by John Wiley & Sons, Inc.